The Effects of Coronavirus on The Profitability of the Banks Operating in Jordan: An Empirical study - Kerroucha, Fatima Zohra; Abbassia, Rechache; Zohra, Dich Fatima (Technium Social Sciences Journal, 2022)
This paper investigates the impact of the COVID-19 pandemic on the profitability of the banking sector in Jordan, given the paucity of empirical research on the impact of the COVID 19 pandemic on profitability bank in the context of developing countries. To achieve the search objective, the study selects all Jordanian banks listed in Amman stock exchange during period from 2018 until the year of emergence of corona pandemic 2020 to cover the requirements of statistical and financial analysis. The results study show that the financial indicators extracted from the financial reports of Jordanian banks from 2018-2020 had a decline in value during the year 2020 which corresponds to the emergence of coronavirus pandemic which means that the first hypothesis is valid. Our analysis shows that net profit ant total revenue and provision for credit and return on equity affect significantly the profitability banks. The value of profitability banks at the Amman stock exchange amounts to 68.5 %, while the remaining of 31.5 % refers to other variables that were not included in the construction of the study model. Keyword: Profitability, Jordanian banks, coronavirus pandemic, financial reports, Amman stock exchange